1976
DOI: 10.1021/jf60205a057
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of acid-solubilized gluten

Abstract: 15 30 40 46 46 46 46 46 46 0.1 N HC1 180 30 46 46 46 46 46 46 46 46 0.5 N HC1 80 40 45 46 46 46 46 46 46 46 0.02 N HC1 560

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 14 publications
6
65
0
Order By: Relevance
“…23,24 We observe that, with the same hydrolytic conditions, and when the deamidation time is increased, the emulsion capacity is enhanced (Table 2, lines 5, 11). This corresponds to previously reported data obtained with different experimental conditions by Wu et al, 25 Matsudomi et al 23 and Popineau et al…”
Section: Emulsifying Propertiessupporting
confidence: 93%
“…23,24 We observe that, with the same hydrolytic conditions, and when the deamidation time is increased, the emulsion capacity is enhanced (Table 2, lines 5, 11). This corresponds to previously reported data obtained with different experimental conditions by Wu et al, 25 Matsudomi et al 23 and Popineau et al…”
Section: Emulsifying Propertiessupporting
confidence: 93%
“…Chemical deamidation of gluten removes the amide from glutamine or asparagine, forming the corresponding carboxylic acid, glutamate or aspartate, together with free ammonia. This process changes the potential charge and thus increases the solubility of gluten [14, 15]. Acid hydrolysis of gluten induces emulsifying properties which makes it useful in different kinds of food products, but also in personal care products for the hair and body [16].…”
Section: Introductionmentioning
confidence: 99%
“…12 Little information is available on the deamidation of proteins with acetic acid. Wu et al 8 found that 1.75 mol L −1 acetic acid could replace HCl in the preparation of soluble gluten with good functional properties at 121…”
Section: Introductionmentioning
confidence: 99%
“…However, the water-insoluble characteristic of wheat gluten due to its high Gln and Asn content (∼500 mg g −1 ) strongly limits its extensive use in food processing. Wu et al 8 indicated that promising areas for industrial food or non-food applications of wheat gluten had to be based on prior chemical modification of proteins. This necessitates further studies on the physicochemical properties of proteins deamidated with acetic acid.…”
mentioning
confidence: 99%